A meta-analysis of brain morphometric aberrations in adolescents who experienced childhood trauma - Tymofiyeva, Olga; Hu, Rebecca; Kidambi, Roma; Nguyen, Ca; Max, Jeffrey E.; Yang, Tony T. (Frontiers in Human Neuroscience, 2022)
Introduction Childhood trauma is known to have dramatic effects on the risks for developing psychiatric disorders and increased suicidality. We conducted a meta-analysis of whole brain voxel-based morphometry (VBM) correlates of childhood trauma in adolescents exposed to childhood maltreatment (N = 379) and unexposed controls (N = 348). Methods Anisotropic effect size-signed differential mapping (AES-SDM) was utilized to synthesize the studies. Results We observed increased volume amongst adolescents with a history of childhood trauma in regions that are involved in motor functions and language production: left precentral gyrus, including part of the left inferior frontal gyrus, left fibers of the body of corpus callosum, and left postcentral gyrus. We observed decreased volume amongst adolescents with a history of childhood trauma in regions that are involved in language processing and/or sensory processing: bilateral cerebellum, bilateral middle temporal gyrus, left rostrum of corpus callosum, and bilateral supramarginal gyrus. Discussion We suggest that these morphometric differences may be reflective of impaired motor development and increased sensory sensitivity and hypervigilance in adolescents with experiences of childhood trauma. Our results differ from meta-analytical findings in adults with history of childhood trauma and may contribute to a better understanding of neural mechanisms of childhood trauma, prediction of neurodevelopmental outcomes, and development of more effective and personalized therapies.